Feasibility Test for Android-Based Mobile Learning on High School Content - I Dewa Putu Nyeneng; Afif Rahman Riyanda; Kartini Herlina (Jurnal Pembelajaran Fisika, 2020)
This study explores Android-based mobile learning media design on electrical content. The Media is designed to contain electrical content that is abstract and can not be seen with the naked eye. The content is depicted in a tangible and easily understood by students. The methods used in the development of the research media are Research and Development (R&D), and the development model conducted in this study is the IDI (Instructional Development Institute) Model of research results shows that the media Learning on electrical content is considered valid and the media is easy to use for students and teachers in the learning process.Keywords: learning Media, Mobile Learning, Android, electricityDOI: http://dx.doi.org/10.23960/jpf.v8.n2.202003